Patient-controlled analgesia with and without transverse abdominis plane and rectus sheath space block in cirrhotic patients undergoing liver resection - Yassen, Khaled (J Anaesthesiol Clin Pharmacol, 2019)
BACKGROUND AND AIMS: Optimal pain control can be a challenge in cirrhotic patients. The aim was to compare the analgesic efficacy and side effects of intravenous fentanyl patient-controlled analgesia (PCA) with and without bupivacaine boluses in transversus abdominis plane (TAP) and rectus sheath space (RSB) in cirrhotics undergoing liver surgery. MATERIAL AND METHODS: A double-blinded randomized controlled trial (n = 55, child's A) was conducted. Catheters were inserted surgically in TAP and rectal sheath space during surgical closure. Fentanyl PCA + TAP + RSB group (gp) (n = 30): (0.2 ml/kg of 0.25% bupivacaine, 8 hourly) was compared with fentanyl PCA gp (n = 25): [0.2 ml/kg of saline (placebo) injected in catheters 8 hourly] for 48 h postoperatively. Plasma bupivacaine was measured with an enzyme-linked immunosorbent assay at 10 min, 30 min, 1 h, 2 h, and 4 h after each injection and 30 min before next injection. RESULTS: Fentanyl consumption was reduced in (PCA + TAP + RSB) gp compared to PCA gp (Day 1: 325.4 ± 169.1 vs. 1034 ± 231.7, Day 2: 204.44 ± 62.9 vs. 481.6 ± 158.3 μg, P < 0.05). Both groups demonstrated effective pain control at rest [Visual Analog Scales (VAS) <3), but on movement pain control with bupivacaine was better (P < 0.05). Increased demand for rescue opioids was observed prior to next scheduled bupivacaine injection in 10/30 patients on Day 1 and 2/30 on Day 2, in association with a reduced bupivacaine serum levels compared to 10 min after injection (47.6 ± 22.7 vs. 93.6 ± 61.0 ng/ml, respectively, P < 0.05). Bupivacaine did not exceed referred toxic levels. CONCLUSION: Repeated bupivacaine TAP and RSB with PCA fentanyl improved pain control, reduced opioids demand with no toxicity. Time interval between injections needs to be reduced to avoid breakthrough pain.